2008
DOI: 10.1080/11250000801886254
|View full text |Cite
|
Sign up to set email alerts
|

Assessing species validity ofMugil platanusGünther, 1880 in relation toMugil cephalusLinnaeus, 1758 (Actinopterygii)

Abstract: Conservative morphological characters make identification of mullet species difficult. As a consequence, cosmopolitan distribution of Mugil cephalus is currently under discussion. In order to clarify the controversy regarding the taxonomic status of the southern Atlantic American mullet M. platanus, in relation to Mugil cephalus, a comprehensive analysis is presented using sequences of the mitochondrial gene cytochrome b, landmark-based morphometry and meristic data. The interlandmark distances showed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This number of scales on the lateral line has already been quoted by different authors to be among the most discriminating characters between Mugil platanus and M. cephalus (Castro et al, 2008), as well as between Mugil platanus and M. liza, as Cousseau et al (2005) and Menezes (1983) pointed out. In groups X1 and X2, the number of lateral line scales overlap significantly.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This number of scales on the lateral line has already been quoted by different authors to be among the most discriminating characters between Mugil platanus and M. cephalus (Castro et al, 2008), as well as between Mugil platanus and M. liza, as Cousseau et al (2005) and Menezes (1983) pointed out. In groups X1 and X2, the number of lateral line scales overlap significantly.…”
Section: Discussionmentioning
confidence: 92%
“…This study has demonstrated morphological differences between the 3 related groups (X1, X2, and X3). Similarly, Heras et al (2006) demonstrated morphometric differences between M. cephalus and M. curema, and Castro et al (2008) between M. cephalus and M. platanus. On this basis, and supported by descriptions by Diouf (1991), Albaret (2003), Harrison (2007), and Castro et al (2008), individuals of group X3 could therefore be assigned to the species Mugil cephalus, those of group X1 to the species M. curema, and individuals in group X2 to the species M. bananensis.…”
Section: Discussionmentioning
confidence: 99%
“…He stated that in using the key it is necessary to compare specimens of the same size for a reliable use of proportional measurements. It is widely recognized that morphometric characters are diagnostically useful when the number of specimens examined is adequate and the methods can be statistically tested (Inada, 1981;Cousseau et al, 2005;Heras et al, 2006;González Castro et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The extremely wide distribution of a number of coastal fish species might be indeed an artifact, as they could be actually constituted by more than a single species (Gill & Kemp 2002). Therefore, the wide geographic distribution of many marine species requires careful re-evaluation, and is certainly necessary for the grey mullet Mugil cephalus Linnaeus, 1758. nomic status of M. platanus, with some authors considering it in synonymy with the cosmopolitan M. cephalus (Thomson 1997;Harrison 2002;Menni 2004) and others indicating it as a different species (Menezes 1983;Cousseau et al 2005;González Castro et al 2008). Conversely, there is no taxonomic ambiguity between M. cephalus and M. liza, because they are both considered valid species, occurring in sympatry in the Gulf of Mexico (Mefford 1955;Ditty & Shaw 1996;Harrison 2002), that differ in the number of lateral series scales (LTS ≤ 34 and LTS > 34, respectively) (Thomson 1997).…”
Section: Introductionmentioning
confidence: 99%